1999
DOI: 10.1029/1999gl010827
|View full text |Cite
|
Sign up to set email alerts
|

A 22° long seismic profile for the study of the top of D'

Abstract: length smaller than 1ø). The first onset times observed at distances larger than 85 ø are compatible with a D" velocity about 1% larger than standard models along these paths, up to a depth of 2850 km. By one dimensional forward modeling we find one model with a 2.8% discontinuity at 2605 km depth, another with a 7 km thick 3% low velocity lamella at 2607 km depth. They both generate waveforms which fit the data similarly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(2 reference statements)
1
8
0
Order By: Relevance
“…We show PK d KP traveltimes for the model PWDK [ Davis and Weber , 1990] and a model (PSA1) that provides a slightly better fit to the data in Figure 4a due to smaller traveltime and slowness. PSA1 is similar to several other models of D″ in different regions of the Earth [ Young and Lay , 1987b; Gaherty and Lay , 1992; Sidorin et al , 1999; Freybourger et al , 1999]. The two models PWDK and PSA1 differ only slightly in the depth of the D″ discontinuity but strongly in regard to the velocity gradients.…”
Section: Traveltimessupporting
confidence: 71%
“…We show PK d KP traveltimes for the model PWDK [ Davis and Weber , 1990] and a model (PSA1) that provides a slightly better fit to the data in Figure 4a due to smaller traveltime and slowness. PSA1 is similar to several other models of D″ in different regions of the Earth [ Young and Lay , 1987b; Gaherty and Lay , 1992; Sidorin et al , 1999; Freybourger et al , 1999]. The two models PWDK and PSA1 differ only slightly in the depth of the D″ discontinuity but strongly in regard to the velocity gradients.…”
Section: Traveltimessupporting
confidence: 71%
“…The variations in depth of the discontinuity are uncertain due to the lack of constraint on velocity above and below the discontinuity, but some variation appears to exist. Thin high-velocity or low-velocity lamella models appear to fit some P-wave observations at least as well as first-order velocity discontinuity models (Freybourger et al, 1999;Thomas et al, 1998;Weber, 1994), but this has not been demonstrated convincingly for S-wave observations. It has been argued that the D 00 discontinuities are actually globally extensive, with lateral variations in depth and strength being the result of lateral temperature variations and interactions with upwelling and downwelling flow (e.g., Nataf and Houard, 1993;Sidorin et al, 1998Sidorin et al, , 1999.…”
Section: Seismic Wave Triplicationsmentioning
confidence: 89%
“…The reflector that produces this extra arrival varies globally in depth by several Depth (km) Figure 6 Radial profiles of S-wave velocity in the lowermost mantle: PREM (Dziewonski and Anderson, 1981), SLHE, SLHA (Lay and Helmberger, 1983a), SYL1 (Young and Lay, 1987a), SGHP (Garnero et al, 1988), SWDK (Weber and Davis, 1990), SYLO (Young and Lay, 1990), and SGLE (Gaherty and Lay, 1992). hundred kilometers (e.g., Kendall and Shearer, 1994) and appears to have regional-scale lateral variations of on the order of a hundred kilometers that may produce scattering rather than simple reflections (e.g., Emery et al, 1999;Freybourger et al, 1999;Hutko et al, 2006;Krü ger et al, 1995;Lay et al, 1997Lay et al, , 2004aScherbaum et al, 1997;Thomas et al, 2004a,b;Weber, 1993;Yamada and Nakanishi, 1998). Shear velocity increases of 2.5-3.0% are found in regions under Eurasia (SWDK and SGLE), Alaska (SYLO), Central America (SLHA), the Indian Ocean (SYL1), and the central Pacific (SGHP).…”
Section: Seismic Wave Triplicationsmentioning
confidence: 99%
“…Siberia is not entirely unexplored in terms of lower mantle and CMB structure. The lowermost mantle under Siberia has been examined in several studies of earthquake P wave data from the Pacific subduction zones recorded at various sites in western Europe [ Weber and Davis , 1990; Gaherty and Lay , 1992; Weber , 1993; Thomas and Weber , 1997; Thomas et al , 1998; Freybourger et al , 1999, 2001; Thomas et al , 2002]. The reflection points for PcP are clustered around 80°E mostly under Siberia and the Kara Sea, east of the trace of the Ural Mountains and north of the location of the Peaceful Nuclear Explosion profiles.…”
Section: Introductionmentioning
confidence: 99%